2022
DOI: 10.1111/jog.15507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic enclosed electromechanical morcellation and vaginal enclosed scalpel morcellation at laparoscopic myomectomy: A prospective randomized trial

Abstract: Aim: This study aimed to compare the laparoscopic-enclosed electromechanical morcellation (LEM) with vaginal-enclosed scalpel morcellation (VSM) in laparoscopic myomectomy procedures. Methods: One hundred eighteen patients who underwent laparoscopic myomectomy were enrolled the prospective randomized interventional clinical study in tertiary university hospital. After myomectomy, tissue removal was accomplished via either LEM using the in-glove morcellation technique or VSM. Results: The median tissue removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In recent years, laparoscopic myomectomy for the treatment of uterine fibroids has been investigated extensivel 6 26. Numerous studies have shown that laparoscopic myomectomy is a minimally invasive and effective treatment for uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, laparoscopic myomectomy for the treatment of uterine fibroids has been investigated extensivel 6 26. Numerous studies have shown that laparoscopic myomectomy is a minimally invasive and effective treatment for uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%